Is Nox the source of ROS involved in Glut1 activity in B1647 cells? - Prata, Cecilia (Acta Biologica Szegediensis, 2006)
The discovery of a family of superoxide-generating enzymes, homologues of ABSTRACT phagocyte oxidase, has led to the concept that ROS are “intentionally” generated with biological functions in various cell types. We have recently shown that, in two leukaemic cell lines (M07e and B1647), there is a correlation between ROS and an important physiological activity, like glucose uptake, which is up-regulated in leukaemic cells. In this study, we tried to elucidate the sources of ROS generation and the mechanisms by which ROS are involved in the regulation of glucose uptake in B1647 cells. In particular, we investigated the presence and the role of a member of the NAD(P)H oxidase family (Nox). Data obtained in the presence of Nox inhibitors suggest that ROS involved in glucose uptake could be generated by this membrane-bound enzymatic complex. The effects of tyrosine kinase inhibitors and antioxidants show the importance of phosphorylation processes in the regulation of glucose uptake. PI3-kinase seems to be involved in ROS generation, possibly through Rac, which binds to Nox. The activation of tyrosine kinase receptor by vascular endothelium growth factor (VEGF), produced by an autocrine pathway in this cell line, seems to be an important step of this pathway.